Pengaruh Pendidikan Pedoman Gizi Seimbang dengan Menggunakan Puzzle terhadap Pengetahuan Siswa SD Swasta Al Fitriah Medan - Emi Inayah Sari Siregar; Tinah Tinah (Universitas Batanghari Jambi, 2021)
This research aims to determine the education effect of balanced nutrition guidelines using puzzle on Al Fitriah Private Elementary School Students, Medan. The type of research used is quasi experiment. The study was conducted on 45 students using a questionnaire before and after the intervention. The statistical test used is a paired t-test. The results showed an average score of respondents knowledge before being given nutrition education by 10.96 and increasing after being given nutrition education using puzzle media to 16.84. The results of the analysis using paired sample t test obtained a value of p = 0,000 where p <0.005. So it can be concluded that there is a significant difference in the variable knowledge of fifth grade students of Al Fitriah Medan Private Elementary School before and after being given nutrition education using puzzle media.